Recent progress in combination therapy of oncolytic vaccinia virus - Mirbahari, Seyedeh Nasim; Da Silva, Miles; Zúñiga, Abril Ixchel Muñoz; Kooshki Zamani, Nika; St-Laurent, Gabriel; Totonchi, Mehdi; Azad, Taha (Frontiers in Immunology, 2024)
In recent years, oncolytic viruses have emerged as promising agents for treating various cancers.An oncolytic virus is a non-pathogenic virus that, due to genetic manipulation, tends to replicate in and cause lysis of cancerous cells while leaving healthy cells unaffected. Among these viruses, vaccinia virus is an attractive platform for use as an oncolytic platform due to its 190 Kb genome with a high capacity for encoding therapeutic payloads. Combining oncolytic VV therapy with other conventional cancer treatments has been shown to be synergistic and more effective than monotherapies. Additionally, OVV can be used as a vector to deliver therapeutic payloads, alone or in combination with other treatments, to increase overall efficacy. Here, we present a comprehensive analysis of preclinical and clinical studies that have evaluated the efficacy of oncolytic vaccinia viruses in cancer immunotherapy. We discuss the outcomes of these studies, including tumor regression rates, overall survival benefits, and long-term responses. Moreover, we provide insights into the challenges and limitations associated with oncolytic vaccinia virusbased therapies, including immune evasion mechanisms, potential toxicities, and the development of resistance.